Non-negligible health risks caused by inhalation exposure to aldehydes and ketones during food waste treatments in megacity Shanghai. (15th May 2023) - Zhang, Liangmao; Wang, Binghan; Li, Kaiyi; Wang, Zijiang; Xu, Dan; Su, Yinglong; Wu, Dong; Xie, Bing
Abstract: Aldehydes and ketones in urban air continue to receive regulatory and scientific attention for their environmental prevalence and potential health hazard. However, current knowledge of the health risks and losses caused by these pollutants in food waste (FW) treatment processes is still limited, especially under long-term exposure. Here, we presented the first comprehensive assessment of chronic exposure to 21 aldehydes and ketones in urban FW-air environments (e.g., storage site, mechanical dewatering, and composting) by coupling substantial measured data (383 samples) with Monte Carlo-based probabilistic health risk and impact assessment models. The results showed that acetaldehyde, acetone, 2-butanone and cyclohexanone were consistently the predominant pollutants, although the significant differences in pollution profiles across treatment sites and seasons (Adonis test, P  < 0.001). According to the risk assessment results, the estimated cancer risk (CR; mean range: 1.6 × 10 −5 -1.12 × 10 −4 ) and non-cancer risk (NCR; mean range: 2.98–22.7) triggered by aldehydes and ketones were both unacceptable in most cases (CR: 37.8%–99.3%; NCR: 54.2%–99.8%), and even reached the limit of concern to CR (1 × 10 −4 ) in some exposure scenarios (6.18%–16.9%). Application of DALYs (disability adjusted life years) as a metric for predicting the damage suggested that exposure of workers to aldehydes and ketones over 20 years of working in FW-air environments could result in 0.02–0.14 DALYs per person. Acetaldehyde was the most harmful constituent of all targeted pollutants, which contributed to the vast majority of health risks (>88%) and losses (>90%). This study highlights aldehydes and ketones in FW treatments may be the critical pollutants to pose inhalation risks. Graphical abstract: Image 1 Highlights: Treatment strategies and temperature were critical in shaping pollution profiles. Available mask appeared less efficacious for aldehydes and ketones removal. Chronic cancer risk and non-cancer risk were unacceptable in most cases. Average annual health loss for 100, 000 workers was between 90 and 720 years. Acetaldehyde contributed to the vast majority of health risks and losses.